The implementation potential of a method to monitor empirically-supported children's mental health treatment through claims data - Sarah Cusworth Walker; Noah Gubner; Aniyar Iztguttinov; Felix Rodriguez; Paul Davis; Aaron Lyon; Suzanne Kerns; Eric Bruns; Jiage Qian; Georganna Sedlar (BMC, 2021)
Abstract Background The delivery of evidence-supported treatments (EST) in children's mental health could be a valuable measure for monitoring mental healthcare quality; however, efforts to monitor the use of EST in real world systems are hindered by the lack of pragmatic methods. This mixed methods study examined the implementation and agency response rate of a pragmatic, claims-based measure of EST designed to be applied as a universal quality measure for child psychotherapy encounters in a state Medicaid system. Methods Implementation potential of the EST measure was assessed with healthcare leader rankings of the reporting method's acceptability, appropriateness and feasibility (n = 53), and post-implementation ratings of EST rate accuracy. Ability of the healthcare system to monitor EST through claims was measured by examining the agency responsivity in using the claims-based measure across 98 Medicaid-contracted community mental health (CMH) agencies in Washington State. Results The analysis found the reporting method had high implementation potential. The method was able to measure the use of an EST for 83% of children covered by Medicaid with 58% CMH agencies reporting > 0 ESTs in one quarter. Qualitative analyses revealed that the most significant barrier to reporting ESTs was the operability of electronic health record systems and agencies' mixed views regarding the accuracy and benefits of reporting. Conclusions Measurement of child mental health ESTs through Medicaid claims reporting has acceptable implementation potential and promising real world responsiveness from CMH agencies in one state. Variation in reporting by agency site and low to moderate perceived value by agency leaders suggests the need for additional implementation supports for wider uptake.